Intelligence, emotional intelligence, and emo-sensory intelligence: Which one is a better predictor of university students’ academic success? - Pishghadam, Reza; Faribi, Maryam; Kolahi Ahari, Mahtab; Shadloo, Farzaneh; Gholami, Mohammad Javad; Shayesteh, Shaghayegh (Frontiers in Psychology, 2022)
The primary aim of this study was to determine the role of psychometric intelligence (IQ), emotional intelligence (EQ), and emo-sensory intelligence (ESQ) in university students’ academic achievement. To this end, 212 university students at different academic levels, composed of 154 females and 58 males, were asked to complete the Raven’s Progressive Matrices, the Bar-On Emotional Quotient Inventory, and the Emo-Sensory Intelligence Scale. Data were then matched with students’ Grade Point Averages as a measure of their academic achievement. The results revealed that students’ level of IQ and EQ could positively predict their academic achievement. In the case of their ESQ level, its auditory sub-component was found to be a positive predictor of academic success. Results were discussed, and possible implications and applications for increasing students’ chances for success were presented.